Exploring genomic resistance to coinfection: Single or dual pathogen infection by Ostreid Herpesvirus 1 and Vibrio aestuarianus in Pacific oysters Crassostrea gigas - Antoine Jourdan; Florence Phocas; Pierre Boudry; Pierrick Haffray; François Allal; Elise Maurouard; Serge Heurtebise; Benjamin Morga; Lionel Dégremont; Romain Morvezen (Aquaculture, 2026)

Bacteria with antibacterial activities isolated from Magallana gigas microbiota as potential probiotics against Vibrio aestuarianus infections in oyster farming - Luc Dantan; Marie-Agnès Travers; Lionel Degremont; Benjamin Morga; Prunelle Carcassonne; Mickael Mege; Yannick Fleury; Bruno Petton; Elise Maurouard; Jean-François Allienne; Gaëlle Courtay; Océane Romatif; et al. (Aquaculture, 2025)

Deciphering the molecular mechanisms of oyster resistance to Pacific Oyster Mortality Syndrome (POMS) disease induced by high temperatures - Léo Duperret; Alejandro Valdivieso; Emily Kunselman; Bruno Petton; Benjamin Morga; Julien de Lorgeril; Fabrice Pernet; Lionel Degremont; Nicole Faury; Jean-François Allienne; Juliette Pouzadoux; Océane Romatif; et al. (Science of The Total Environment, 2025)

Prokaryotic microbiota outperform eukaryotic microbiota in differentiating between infection states of iconic diseases of two commercial oyster species - K. Mathias Wegner; Benjamin Morga; Laure Guillou; Martina Strittmatter; Cyrielle Lecadet; Marie-Agnes Travers; Delphine Tourbiez; Ophélie Gervais; Isabelle Arzul (Aquaculture, 2025)

DNA methylation landscapes before and after Pacific Oyster Mortality Syndrome are different within and between resistant and susceptible Magallana gigas - Alejandro Valdivieso; Benjamin Morga; Lionel Degremont; Mickaël Mege; Gaëlle Courtay; Yann Dorant; Jean-Michel Escoubas; Janan Gawra; Julien de Lorgeril; Guillaume Mitta; Celine Cosseau; Jeremie Vidal-Dupiol (Science of The Total Environment, 2025)

Trained immunity: Perspectives for disease control strategy in marine mollusc aquaculture - Caroline Montagnani; Benjamin Morga; Beatriz Novoa; Benjamin Gourbal; Amaro Saco; Magali Rey‐Campos; Marion Bourhis; Fabien Riera; Emmanuel Vignal; Charlotte Corporeau; Guillaume M. Charrière; Marie‐Agnès Travers; et al. (Reviews in Aquaculture, 2024)
Recent evidence has demonstrated the unique properties of the innate immune system, known as innate immune memory, immune priming, or trained immunity. These properties have been described as the ability of the innate immune system to learn from previous microbial experiences, which improves survival after subsequent infection. In this review, we present the state of knowledge on trained immunity in invertebrates and provide a comprehensive overview of these capabilities in cultured marine molluscs, which are currently threatened by recurrent diseases. Studies have shown that exposure to environmental microbiota, pathogens, or derived elements, can provide a stronger response and protection against future infections. These studies highlight common and distinct features of protection, mechanisms, specificity, and duration that vary with immune markers, and methods of stimulation. While the cellular and molecular basis of these responses is only partially understood, effects on phagocytosis, haemocyte populations, apoptosis, oxidative stress, and immune gene expression have been suggested. Finally, we propose a framework for future research to go beyond the current evidence and address potential limitations in the implementation of trained immunity‐based strategies to control disease. Immune training may provide a unique opportunity to promote the sustainable development of marine mollusc aquaculture.

Microbial education for marine invertebrate disease prevention in aquaculture - Luc Dantan; Eve Toulza; Bruno Petton; Caroline Montagnani; Lionel Degremont; Benjamin Morga; Yannick Fleury; Guillaume Mitta; Yannick Gueguen; Jeremie Vidal‐Dupiol; Céline Cosseau (Reviews in Aquaculture, 2024)
The holobiont theory expands the notion of individual multicellular organisms as a community composed of a host and all its associated microorganisms. This concept has been extensively studied in the field of aquaculture, where increasing evidence has highlighted the importance of the host associated microorganisms in species fitness. Here, we focus our review on mollusc and crustacean species in which microbiota dysbiosis has recently been described in the context of various diseases, resulting in significant economic losses. Influencing the holobiont structure through the use of probiotics is a potential strategy that could improve the fitness or the robustness of cultivated species. We discuss here the possibility of developing microbiome targeted prophylactic approaches by promoting (1) methods to identify host microbial community that fosters good health status and (2) early life microbial education to favour long‐term resistance to stress or disease. This review aims to inform the aquaculture industry about potential strategies in rearing practices to mitigate diseases and economic losses.

Antiviral protection in the Pacific oyster Crassostrea (Magallana) gigas against OsHV-1 infection using UV-inactivated virus - Benjamin Morga; Mickäel Mège; Nicole Faury; Lionel Dégremont; Bruno Petton; Jean-François Pépin; Tristan Renault; Caroline Montagnani (Frontiers in Marine Science, 2024)
The increase of the frequency and severity of marine diseases affecting farmed marine mollusks are currently threatening the sustainability of this aquaculture sector, with few available prophylactic or therapeutic solutions. Recent advances have shown that the innate immune system of invertebrates can develop memory mechanisms allowing for efficient protection against pathogens. These properties have been called innate immune memory, immune priming or trained immunity. Previous results demonstrated the possibility to elicit antiviral immune priming to protect Pacific oysters against the ostreid herpes virus 1 (OsHV-1), currently plaguing M. gigas production worldwide. Here, we demonstrate that UV-inactivated OsHV-1 is also a potent elicitor of immune priming. Previous exposure to the inactivated virus was able to efficiently protect oysters against OsHV-1, significantly increasing oyster survival. We demonstrate that this exposure blocked viral replication and was able to induce antiviral gene expression potentially involved in controlling the infection. Finally, we show that this phenomenon can persist for at least 3 months, suggesting the induction of innate immune memory mechanisms. This study unravels new ways to train the Pacific oyster immune system that could represent an opportunity to develop new prophylactic strategies to improve health and to sustain the development of marine mollusk aquaculture.

Resistance to OsHV-1 Infection in Crassostrea gigas Larvae - Lionel Dégremont; Benjamin Morga; Suzanne Trancart; Jean-François Pépin (Frontiers in Marine Science, 2016)